2006
DOI: 10.2478/s11696-006-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Limited sample recovery in coupled methods of high-performance liquid chromatography of synthetic polymers

Abstract: Complex polymer systems, which exhibit multiple distributions in their molecular parameters can be characterized by coupled liquid chromatographic methods. The latter combine entropic (exclusion) and enthalpic (interaction) retention mechanisms. However, recent experimental results suggest that some coupled liquid chromatographic methods may suffer from incomplete sample recovery. This refers, for example, to liquid chromatography under critical conditions of enthalpic interactions and to eluent gradient liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…For low molar mass standards, low oligomers might be evaporated with the mobile phase under the stringent evaporating conditions leading to smaller peak areas compared with some of the high molar mass standards [60]. For higher molar mass standards, the so-called limited recovery of polymers could be a factor, namely, the incomplete elution of some of the injected polymers [61,62]. Previous research within our group has shown that a smaller peak for higher molar masses can also be due to changes in droplet formation as the molar mass increases.…”
Section: Resultsmentioning
confidence: 99%
“…For low molar mass standards, low oligomers might be evaporated with the mobile phase under the stringent evaporating conditions leading to smaller peak areas compared with some of the high molar mass standards [60]. For higher molar mass standards, the so-called limited recovery of polymers could be a factor, namely, the incomplete elution of some of the injected polymers [61,62]. Previous research within our group has shown that a smaller peak for higher molar masses can also be due to changes in droplet formation as the molar mass increases.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial fraction of sample may stay retained in the LC CC column . Detailed studies of this occurrence revealed the fast decrease of sample recovery with the increasing polymer molar mass.…”
Section: Coupled Lc Methodsmentioning
confidence: 99%
“…LC‐CC was also employed at elevated temperature for separation of polyolefins , however the method enables efficient separation of only binary polymer systems. Both LC‐CC and EG‐LC suffer from limited sample recovery .…”
Section: Introductionmentioning
confidence: 99%